2002
DOI: 10.1046/j.1432-1033.2002.03044.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of farnesyldiphosphate synthase and epi‐aristolochene synthase, a sesquiterpene cyclase involved in capsidiol biosynthesis in Nicotiana tabacum

Abstract: A clone encoding farnesyl diphosphate synthase (FPPS) was obtained by PCR from a cDNA library made from young leaves of Artemisia annua. A cDNA clone encoding the tobacco epi-aristolochene synthase (eAS) was kindly supplied by J. Chappell (University of Kentucky, Lexington, KY, USA). Two fusions were constructed, i.e. FPPS/ eAS and eAS/FPPS. The stop codon of the N-terminal enzyme was removed and replaced by a short peptide (Gly-SerGly) to introduce a linker between the two ORFs. These two fusions and the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…The process likely benefits from a proximity effect of the two active sites to reduce loss of intermediates to other competing pathways. Previous attempts to use this concept in vivo have generally been unsuccessful (1,18,36) despite the fact that fusion enzymes have proven superior to free enzymes in several in vitro studies (6,7,22,29). At least two parameters should be considered in order to obtain successful exploitation of fusion proteins in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process likely benefits from a proximity effect of the two active sites to reduce loss of intermediates to other competing pathways. Previous attempts to use this concept in vivo have generally been unsuccessful (1,18,36) despite the fact that fusion enzymes have proven superior to free enzymes in several in vitro studies (6,7,22,29). At least two parameters should be considered in order to obtain successful exploitation of fusion proteins in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A number of observations suggest that this strategy can be used to improve the flux through a metabolic pathway. First, several protein fusions consisting of sequential enzymes have been characterized in vitro and shown to possess kinetic properties superior to those of the individual enzymes (6,7,22,29). Second, experiments carried out with purified fusion proteins in polyethylene glycol solutions to mimic the crowded environment inside the cell indicate that the positive effects of enzyme fusion may be even greater in vivo (38,25,5).…”
mentioning
confidence: 99%
“…Previously, an artificially constructed chimeric enzyme containing an FDP synthase domain and a tobacco epi-aristolochene synthase domain was found to produce the sesquiterpene epiaristolochene from GDP and IPP. 50) This previous study also suggested that the chimeric enzyme was more efficient than a mixture of the two separate enzymes in converting GDP and IPP into epi-aristolochene in vitro. We suggest that multifunctional fungal enzymes exhibiting both prenyltransferase and terpene cyclase activity contribute to the efficient production of bioactive terpenes, regardless of the availability of GGDP in the cell.…”
Section: Labdane-related Diterpene Cyclase Gene Family In Ricementioning
confidence: 90%
“…In an effort to engineer substrate channeling between successive enzymes in a biosynthetic pathway, Brodelius et al fused a C 15 PP synthase with a sesquiterpene cyclase (34). The resultant fusion enzyme was more efficient at converting isopentenyl diphosphate into the cyclized C 15 product than was the corresponding quantity of mixed unfused enzymes (34).…”
Section: Future Challenge: Specific Pathwaysmentioning
confidence: 99%
“…The resultant fusion enzyme was more efficient at converting isopentenyl diphosphate into the cyclized C 15 product than was the corresponding quantity of mixed unfused enzymes (34). Efforts in this direction might better regulate recombinant carotenoid pathways in E. coli, although significant structural information, which is currently unavailable for carotenoid enzymes, may be required.…”
Section: Future Challenge: Specific Pathwaysmentioning
confidence: 99%